2019
DOI: 10.1016/j.cegh.2019.02.002
|View full text |Cite|
|
Sign up to set email alerts
|

REMOVED: Validation of the Hamilton Anxiety Rating Scale and State Trait Anxiety Inventory A and B in Arabic among the Lebanese population

Abstract: Our aim in this study was to translate the Hamilton Anxiety Rating Scale (HAM-A), State Trait Anxiety Inventory (STAI-A and B) scales to Arabic, linguistically validate them for use in a representative sample of the Lebanese population, and to check the reliability of these Arabic versions. Methods: This study is cross-sectional, conducted between November 2017 and March 2018, which enrolled 1332 community dwelling participants using a proportionate random sample from all Lebanese Mohafazat. Results: Three fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…18 Previous study has shown that the Arabic version of HAM-A is reliable and valid with coefficient alpha of 0.921, which is similar to the results obtained from previous research in adults, suggesting that the items of this scale are able to screen for anxiety among Arabic population in an excellent way. 19,20 This study showed a good reliability with a coefficient alpha of 0.89. The fourth part composed of nine questions about the anxiolytics practice including previous use of anti-anxiety drugs or herbs/supplements, thinking of using anti-anxiety drugs or herbs, during quarantine, using anti-anxiety drugs or herbs during quarantine, impressions of students about efficacy and safety of anti-anxiety drugs or herbs and their opinion about the best way to decrease anxiety.…”
Section: Instrumentsmentioning
confidence: 62%
“…18 Previous study has shown that the Arabic version of HAM-A is reliable and valid with coefficient alpha of 0.921, which is similar to the results obtained from previous research in adults, suggesting that the items of this scale are able to screen for anxiety among Arabic population in an excellent way. 19,20 This study showed a good reliability with a coefficient alpha of 0.89. The fourth part composed of nine questions about the anxiolytics practice including previous use of anti-anxiety drugs or herbs/supplements, thinking of using anti-anxiety drugs or herbs, during quarantine, using anti-anxiety drugs or herbs during quarantine, impressions of students about efficacy and safety of anti-anxiety drugs or herbs and their opinion about the best way to decrease anxiety.…”
Section: Instrumentsmentioning
confidence: 62%
“…The HAM-A [56], recently validated in Lebanon [57], consists of 14 items, rated from 0 (symptoms not present) to 4 (very severe symptoms); higher scores reflect higher anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…The second part of the questionnaire consisted of behavioral practices of certain eating habits among participants. Questions about eating disorders were identified from previous articles [4143]. Questions included: “Do you take your weight daily?”, “Do you follow a diet to lose weight?”, “Do you exercise to lose weight?”, “Do you take diet pills to lose weight?”, “Do you take laxatives or vomit to lose weight?”, “Do you starve yourself to lose weight?”…”
Section: Methodsmentioning
confidence: 99%
“…The Hamilton Anxiety Rating Scale (HAM-A), recently validated in Lebanon [43], consists of 14 symptom-defined elements, and targets both psychological and somatic symptoms. Each item is scored on a basic numeric scoring of 0 (not present) to 4 (severe).…”
Section: Methodsmentioning
confidence: 99%